Maximizing Motorcycle Power and Torque with Roller Modifications: Memaksimalkan Tenaga dan Torsi Sepeda Motor dengan Modifikasi Roller - Efendi, Muchammad; Firdaus, Rachmat (Universitas Muhammadiyah Sidoarjo, 2024)
In the automotive world, rapid advancements in motorized vehicle technology necessitate consumers to be selective in vehicle choice. This study examines the performance of motorcycles using modified racing rollers versus standard factory rollers. Focusing on a 150cc matic motorcycle, we analyzed power and torque outputs using rollers of different masses (11g, 16g, and standard 15.5g). Field studies and literature reviews were conducted, employing tools like dynotests to measure performance at RPM ranges from 4,700 to 9,500. Results indicate that the 16g roller achieved the highest torque of 12.45 N/m at 6,800 RPM, while the 11g roller attained 12.09 N/m at 67,300 RPM. The standard 15.5g roller reached 12.07 N/m at 76,400 RPM. This research highlights the impact of roller mass on motorcycle performance, providing valuable insights for enhancing vehicle efficiency and consumer choice. Highlight: 16g roller achieves highest torque of 12.45 N/m at 6,800 RPM. 11g roller reaches torque of 12.09 N/m at 67,300 RPM. Standard 15.5g roller attains 12.07 N/m at 76,400 RPM. Keywoard: Motorcycle Performance, Racing Rollers, Torque, Power Output, 150cc Matic